Hypertension Among Patients With End Stage Renal Disease on Regular Haemodialysis at Gezira Hospital for Renal Diseases and Surgery - Elsharif, Mohamed Elhafiz; Omran, Mustafa; El Imam, Mohamed; Tagelsir, Winy; Elsharif, Elham (مجلة الجزيرة للعلوم الصحية; مجلد 8 عدد 1 (2012), 2012)
Background: The prevalence of hypertension in patients with chronic kidney disease, from all causes, increases linearly as renal function deteriorates, reaching approximately 95% as patients approach end-stage renal disease. Objectives: To determine the incidence of hypertension in patients on  haemodialysis and to evaluate the control of blood pressure among patients with end stage renal disease. Patients and methods: This was a prospective cross sectional study, conducted at Gezira Hospital for Renal Diseases and Surgery, Wad Medani, in January 2010. 133 patients with end stage renal disease were enrolled in this study ,blood pressure was measured pre, intra and post dialysis sessions. Drug therapy and the complications of hypertension were recorded. Results: 89% of all patients were hypertensive, 94.07% out of them were on antihypertensive.  Blood pressure was not adequately controlled in 62.16% of the patients. Paradoxical hypertension was found in 12.78%.14.41% of the hypertensive group admit to have poor compliance for their antihypertensive medications. Calcium channel blockers were used in 42.94%, angiotensin converting enzyme inhibitors 36.72%, beta-blockers 15.26%, angiotensin II receptor in 2.26%,  Alpha blocker in 2.26% and diuretics in 0.07% of the cases. 35.58% of the patients were suffering congestive heart failure and 2.26%  suffered from cerebrovascular accident. Conclusions : The prevalence of hypertension in patients on regular haemodialysis mounting to 90%. ملخص: خلفية :أن شيوع فرط ضغط الدم في مرضى الكلي المزمن بكل أسبابه  يزداد بالتماشي مع التدهور في وظيفة الكلي ليصل حوالي 95% عند مرضى الكلي في المرحلة النهائية. الأهداف : تحديد معدل حدوث فرط ضغط الدم في المرضى تحت المعالجة بالغسيل الدموي  و تقييم التحكم في فرط ضغط الدم في مرضى الكلي نهائي المرحلة. الطرق و المرضى : هذه دراسة توقعية قطاعية اجريت في مستشفى الجزيرة لأمراض  و جراحة الكلي – ود مدني، في يناير 2010م. شملت الدراسة 133 مريض كلي بالمرحلة النهائية . تم قياس ضغط الدم قبل و اثناء و بعد جلسة الغسيل الدموي ، كما تم تدوين المعالجات و أي مضاعفات لفرط ضغط الدم النتائج : 89%من المرضى يعانون فرط ضغط الدم و 94.57 % منهم يتناولون العلاج. ضغط الدم لم يكن متحكماً به على نحو كاف في 62.16% من المرضى ، فرط ضغط الدم المتناقض ظاهرياً وجد في12.78% من الحالات ، 14.41%من المرضى أقروا باستجابتهم الضعيفة في المواظبة بتناول الدواء . الأدوية المستعملة كانت محصرات قنوات الكالسيوم في 42.94%، مثبطات الإنزيم المحول للأنجيوتنسين في 36.72%، محصرات بيتا في 15.26% مستقبلات أنجيوتنسين II  في 2.26%، محصرات ألفا في 2.26%  و مدررات البول في 5.57% . 35.58% من الحالات تعاني هبوط القلب الاحتقاني و 2.26% تعاني من اصابة مخية  وعائية. الخلاصة : شيوع فرط ضغط الدم في المرضى تحت المعالجة بالغسيل الدموي تصل الى 90%.